Evaluasi Benchmarking sebagai Strategi dalam Meningkatkan Keunggulan Bersaing dan Kinerja Bisnis - Anisah, Anisah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to look at the influence of benchmarking on competitive advantage and the influence of both on performance. The research method used is a quantitative descriptive method with a sample of 115 businesses at the middle level. The data collection technique used in this research is a questionnaire and the data analysis technique uses the SEM method. The results of this research prove that there is a positive and significant influence of benchmarking on competitive advantage and competitive advantage on business performance, but benchmarking does not have a positive impact on business performance, unless mediated by the construct of competitive advantage.